Free play in sectors to promote autonomy in children of four years - FIGUEROA CHAMBERGO, Yrma Violeta (2019)
The present research work called: Free play in sectors to promote Autonomy - children of four years - PrivateEducational Institution “Santa Ana School” - Chiclayo – 2018, is theoretically based on the development process ofAutonomy based on Piaget's theory, which considers that children acquire values through their socialization thusdeveloping their autonomy and the theory of Maria Montessori who sustains that the child so that he can learn in amore dynamic and essential way for his age needs the game, stimuli and strategies that lead him to new learnings. The research method used in the present study is pre-experimental, and as a type of research it is applied, the free playworkshop in sectors: "I can do it" was used to obtain results and give a precise conclusion to the problem. Thepopulation and sample consists of 12 boys and girls of 4 years. A list of Pedagogical Achievement Checks was usedas an instrument and workshop of 20 leisure activities based on free play in sectors was applied. Finally, whenapplying the post-test, the 100% level achieved was obtained; when discussion of results and the expected hypothesistest, it can be concluded that the "I can do it" workshop, based on free play in sectors such as strategies, significantlyinfluenced the development of Autonomy in children of 4 years of the Private Educational Institution "Santa AnaSchool" of Chiclayo - 2018. Key words: Free play in sectors, autonomy, strategy.